Seasonal Variations of Phosphorus Species in the Overlying and Pore Waters of the Tuohe River, China - Qing Xu; Xiaoping Yu; Yafei Guo; Tianlong Deng; Yu-Wei Chen; Nelson Belzile (Journal of Chemistry)
Overlying sediment and pore waters were collected in summer and winter at upstream (Jintang) and downstream (Neijiang) sites of the Tuohe River, which is one of the five largest tributaries of the Yangtze River in China. Phosphorus species, including soluble reactive phosphorus (SRP), soluble unreactive phosphorus (SUP), and total dissolved phosphorus (TDP), and some diagenetic constituents including dissolved Fe(II), Mn(II), and sulfide in overlying and pore waters, were measured systematically. The seasonal variations and vertical distributions of phosphorus species in overlying and pore waters at both sampling sites were obtained to elucidate some aspects of the transport and transformations of phosphorus. Based on the profiles of pore and overlying waters as well as the TDN/TDP data during an algal bloom in 2007, it was clearly demonstrated that phosphorus was the main factor limiting the phytoplankton growth in the Tuohe River.